Thomas L. DeLorme and the science of progressive resistance exercise - Todd, J. S.; Shurley, J. P.; Todd, T. C. (The Journal of Strength and Conditioning Research, 2012)
In the latter years of the Second World War, the number of American servicemen who had sustained orthopedic injuries was overwhelming the nation's military hospitals. The backlog of patients was partly because of the sheer number of soldiers involved in the war effort, but it was exacerbated by rehabilitation protocols that required lengthy recovery times. In 1945, an army physician, Dr. Thomas L. DeLorme experimented with a new rehabilitation technique. DeLorme had used strength training to recover from a childhood illness and reasoned that such heavy training would prove beneficial for the injured servicemen. DeLorme's new protocol consisted of multiple sets of resistance exercises in which patients lifted their 10-repetition maximum. DeLorme refined the system by 1948 to include 3 progressively heavier sets of 10 repetitions, and he referred to the program as "Progressive Resistance Exercise." The high-intensity program was markedly more successful than older protocols and was quickly adopted as the standard in both military and civilian physical therapy programs. In 1951, DeLorme published the text Progressive Resistance Exercise: Technic and Medical Application, which was widely read by other physicians and medical professionals. The book, and DeLorme's academic publications on progressive resistance exercise, helped legitimize strength training and played a key role in laying the foundation for the science of resistance exercise.